Antenatal melatonin as an antioxidant in human pregnancies complicated by fetal growth restriction—a phase I pilot clinical trial: study protocol. Issue 12 (23rd December 2013) - Alers, Nicole O; Jenkin, Graham; Miller, Suzanne L; Wallace, Euan M
Abstract : Background: Fetal growth restriction complicates about 5% of pregnancies and is commonly caused by placental dysfunction. It is associated with increased risks of perinatal mortality and short-term and long-term morbidity, such as cerebral palsy. Chronic in utero hypoxaemia, inflammation and oxidative stress are likely culprits contributing to the long-term neurological sequelae of fetal growth restriction. In this regard, we propose that melatonin, a powerful antioxidant, might mitigate morbidity and/or mortality associated with fetal growth restriction. Melatonin has an excellent biosafety profile and crosses the placenta and blood–brain barrier. We present the protocol for a phase I clinical trial to investigate the efficacy of maternal oral melatonin administration in women with a pregnancy complicated by fetal growth restriction. Methods and analysis: The proposed trial is a single-arm, open-label clinical trial involving 12 women. Severe, early onset fetal growth restriction will be diagnosed by an estimated fetal weight ≤10th centile in combination with abnormal fetoplacental Doppler studies, occurring before 34 weeks of pregnancy. Baseline measurements of maternal and fetal well-being, levels of oxidative stress and ultrasound and Doppler measurements will be obtained at the time of diagnosis of fetal growth restriction. Women will then start melatonin treatment (4 mg) twice daily until birth. The primary outcomes are the levels of oxidative stress in the maternal and fetal circulation and placenta. Secondary outcomes are fetoplacental Doppler studies (uterine artery, umbilical artery middle cerebral artery and ductus venosus), fetal biometry, fetal biophysical profile and a composite determination of neonatal outcome. A historical cohort of gestational-matched fetal growth restriction and a healthy pregnancy cohort will be used as comparators. Ethics and dissemination: Ethical approval has been obtained from Monash Health Human Research Ethics Committee B (HREC12133B). Data will be presented at international conferences and published in peer-reviewed journals. Trial registration number: Clinical Trials, protocol registration system: NCT01695070 .